The Influence of Technological Developments on Islamic Religious Education Learning at SMA IT Al-Husnayain - Solih, Muhammad (MANDAILING GLOBAL EDUKASIA, 2024)
Technological advances have brought significant changes in various aspects of life, including in the field of education. This study aims to analyze the influence of technology on education at elementary school age. The use of technology in learning, such as digital devices, the internet, and educational applications, has a positive impact on increasing the effectiveness and efficiency of the teaching and learning process. However, on the other hand, uncontrolled use of technology can also have negative impacts, such as decreased social interaction and increased dependence on digital devices. This study uses a qualitative method with a literature study approach to better understand the benefits and challenges of using technology in elementary education. The results of the study indicate that technology can be a very useful tool in improving the quality of education, as long as its use is supervised and implemented with the right strategy.